Internal and external factors in sharing behaviour of online video advertisements among generation Y in Selangor, Malaysia - Nik Mohd Zainordin, Nik Mohamad Shamim (2021)
In current times, online platforms have become among the most popular tools to advertise products and services. Specifically, marketers widely use online video advertisements (OVAs) to promote their wares, making this medium a topic of interest in marketing research and practice. Notably, consumers’ reactions to OVAs are vital for their efficacy as marketing tools. However, there is a lack of studies on the factors that encourage consumers to watch and share OVAs. Hence, the main research question addressed by the current study was: “What are the factors that affect the sharing behavior of OVAs among Gen Y in Selangor?” To answer this question, the study aimed to examining internal and external factors toward the sharing behavior of OVAs. Following a preliminary review of the literature gaps and practical issues surrounding the sharing behavior of OVAs, the study sought to test the specific factors of consumers underpinned by Theory of Planned Behaviour (TPB) as internal antecedents and Stimulus-Organism- Response Model (S-O-R) as external antecedents. For internal factors influencing the sharing behaviour of OVAs, which were attitude towards OVA characteristics, social influence and its effect on the social norms of OVA acceptance, and self-efficacy and its effect on the perceived behavioral control over OVAs and for external factors is company reputation, brand awareness, and celebrity endorsement. As a boundary condition, the study also included perceived intrusiveness as a moderator between the aforementioned antecedents and the sharing behaviour of OVAs. Adopting a quantitative methodology, questionnaire data from a total of 220 Gen Y respondents was collected in Selangor. Following analysis using SPSS and Structural Equation Modelling in Smart- PLS, the results showed that attitude and social norms significantly and positively predict consumers’ intention to share OVAs, while there was no such predictive impact of perceived behavioural control. Meanwhile, in terms of external antecedents, only celebrity endorsements were found to positively influence the sharing intention of OVAs. The study also revealed that perceived intrusiveness negatively moderates the effects of attitude and social norms on the intention to share OVAs. Theoretically, the study extends the TPB and S-O-R model in predicting OVA sharing behavior. It also underscores that OVAs perceived as intrusive can diminish the efficacy of advertising on this platform. The findings from this study are useful for marketing practitioners to focus on enhancing consumers’ attitudes, developing social norms surrounding their brand, employing celebrity ambassadors, and minimising intrusiveness in their OVAs. Based on these findings, marketers can appropriately strategize their marketing communication messages to influence consumers to watch and share OVAs.